Chaetomium pneumonia in patient with acute myeloid leukaemia. Issue 2 (February 1996) - Yeghen, T; Fenelon, L; Campbell, C K; Warnock, D W; Hoffbrand, A V; Prentice, H G; Kibbler, C C
Abstract : A patient with relapsed refractory acute myeloid leukaemia developed typical fungal lung lesions despite intravenous amphotericin B prophylaxis. Chaetomium globosum was cultured from the resected right lower lobe. Histology showed branching hyphae negative for common Aspergillus species by immunohistochemical staining. Previous reports of invasive disease caused by Chaetomium and some applications of immunohistochemical staining for Aspergillus are discussed.